Line Source Scattering by Dielectric Objects inside a Circular Cylinder with Resistive Boundary - Part 1: Forward Scattering - (:unkn) unknown (Institute of Electrical and Electronics Engineers Inc., 2019)
In this two-part paper, direct and inverse scattering problems of cylindrical bodies of arbitrary cross section embedded in a circular cylinder with resistive boundary are presented. This work is an extension of the paper Yelkenci [1] to the case of a time-harmonic line source illumination. The numerical data needed for the implementation of the inverse problem are supplied artificially by the approximate numerical solution of the corresponding direct scattering problem. In Part-1, the forward problem is addressed. Part-2 will consider the inverse problem. © 2019 Chamber of Turkish Electrical Engineers.